Clinical Significance of IL-23 Regulating IL-17A and/or IL-17F Positive Th17 Cells in Chronic Periodontitis - Luo, Zhenhua; Wang, Hui; Wu, Yunlong; Sun, Zheng; Wu, Yafei (Mediators of Inflammation, 2014)
Objective. To investigate the expression level and clinical significance of (IL-17A+ and/or IL-17F+) Th17 cells under IL-23 regulation in patients of chronic periodontitis (CP) and healthy controls (HC). Materials and Methods. The whole peripheral blood samples were collected from 30 CP patients and 25 healthy controls. Flow cytometry was used to test the (IL-17A+ and/or IL-17F+) Th17 expression level. Recombinant human IL-23 (rhIL-23) was used to detect Th17 differentiation and expansion. Correlation coefficient analysis between Th17 expression level and clinical parameters was analyzed by SPSS software. Results. Flow cytometry results showed that IL-17A+IL-17F− and IL-17A−IL-17F+ Th17 were both increased in CP group than in HC group (P < 0.01), while, under recombinant human IL-23 (rhIL-23) stimulation, the number of IL-17A+IL-17F− Th17 cells was significantly increased in both CP and HC groups (P < 0.01). Interestingly, IL-17A−IL-17F+ Th17 cells were only increased in CP group after rhIL-23 stimulation. Additionally, correlation coefficient analysis showed significant correlation between IL-17A+IL-17F− Th17 cell and attachment loss or probing depth (P < 0.05). Conclusions. This study indicates that both the IL-17A+IL-17F− and IL-17A−IL-17F+ Th17 cells may be involved in pathogenesis of periodontitis. The role of these Th17 cells in the disease pathogenesis needs to be further investigated.